1997
DOI: 10.1063/1.869182
|View full text |Cite
|
Sign up to set email alerts
|

Thermocapillary motion of deformable drops at finite Reynolds and Marangoni numbers

Abstract: We present the results of numerical simulations of the three-dimensional thermocapillary motion of deformable viscous drops under the influence of a constant temperature gradient within a second liquid medium. In particular, we examine the effects of shape deformations and convective transport of momentum and energy on the migration velocity of the drop. A numerical method based on a continuum model for the fluid–fluid interface is used to account for finite drop deformations. An oct-tree adaptive grid refinem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
65
4

Year Published

1998
1998
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(77 citation statements)
references
References 21 publications
8
65
4
Order By: Relevance
“…It is clear that the scaled migration velocities slightly increase with increasing values of Re 1 , which is similar to the results in Ref. 16, and these increasing rates of final speeds are higher for larger values of Ma 1 . The Ma 1 = 100 runs have not been calculated long enough to reach their final states, but we can roughly draw the similar conclusions.…”
Section: -11supporting
confidence: 78%
See 1 more Smart Citation
“…It is clear that the scaled migration velocities slightly increase with increasing values of Re 1 , which is similar to the results in Ref. 16, and these increasing rates of final speeds are higher for larger values of Ma 1 . The Ma 1 = 100 runs have not been calculated long enough to reach their final states, but we can roughly draw the similar conclusions.…”
Section: -11supporting
confidence: 78%
“…Numerical simulations on the three-dimensional thermocapillary motion of deformable viscous drops were reported by Haj-Harir et al 16 They used the level-set method to catch the interface and found that the strong heat convection may retard the thermocapillary motion of the drop be- cause the isotherms get wrapped around the front surface of the drop and reduce the surface temperature gradient. Nas 17,18 calculated the thermocapillary interaction of multidrops with the front-tracking finite-difference methods.…”
Section: Introductionmentioning
confidence: 99%
“…Since the YGB theory was published, there have been many studies on this problem using theoretical, experimental and numerical tools (see Balasubramaniam & Chai 1987;Chen & Lee 1992;Treuner et al 1996;Haj-Hariri, Shi & Borhan 1997;Welch 1998;Wozniak et al 2001;Sun & Hu 2002Nas, Muradoglu & Tryggvason 2006;Borcia & Bestehorn 2007;Liu, Zhang & Valocchi 2012;Liu et al 2013). Most early findings have been summarized and discussed in the review book by ; see also Subramanian, Balasubramaniam & Wozniak (2002).…”
mentioning
confidence: 99%
“…Front tracking requires the solution of Poisson's equation on the entire fluid grid at every time step, and is thus more costly to implement. Recently, HajHariri et al 28 have developed an adaptive grid refinement scheme in combination with a front tracking method to study thermocapillary motion of drops where the ratio of internal to external fluid viscosity varied from 10 −3 to 10 1 . The immersed boundary method has also been used to simulate the flow of suspensions of solid particles, 29 and the deposition of nondeforming particles on solid substrates in the simulation of biofilm processes.…”
Section: Introductionmentioning
confidence: 99%